2021
DOI: 10.1016/j.ejro.2021.100326
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal gastrointestinal imaging findings on computed tomography in patients with COVID-19 and correlation with clinical outcomes

Abstract: Pulmonary imaging finding of Coronavirus disease 2019 (COVID-19) has been widely described, but until now few studies have been published about abdominal radiological presentation. The aim of this study was to provide an overview of abdominal imaging findings in patients with COVID-19 in a multicenter study and correlate them with worse clinical outcomes. Materials and methods: This retrospective study included adult COVID-positive patients with abdominal CT performed from 4/1/2020 to 5/1/2020 from two institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 23 publications
1
26
0
5
Order By: Relevance
“…Along with ischemic complications, CT scan can also depict hemorrhagic complications such as hematomas or hemorrhagic transformation of bowel ischemia[ 21 ]. Besides its diagnostic role, abdominal imaging has also demonstrated prognostic value upon detection of ischemic gastrointestinal complications in COVID-19, which has been shown to be associated with higher mortality[ 32 , 33 ]. The most frequent findings on abdominal imaging in COVID-19 are summarized in Figure 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Along with ischemic complications, CT scan can also depict hemorrhagic complications such as hematomas or hemorrhagic transformation of bowel ischemia[ 21 ]. Besides its diagnostic role, abdominal imaging has also demonstrated prognostic value upon detection of ischemic gastrointestinal complications in COVID-19, which has been shown to be associated with higher mortality[ 32 , 33 ]. The most frequent findings on abdominal imaging in COVID-19 are summarized in Figure 1 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Horvat et al found the presence of intestinal findings on CT in hospitalized COVID-19 patients positively correlated with a higher risk of worse clinical outcome including death or assisted ventilation (64).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 98%
“…The most common and consistently reported imaging manifestations of COVID-19 affecting the bowel include mural thickening, non-specific ileus, fluid-filled colon, and pneumatosis intestinalis. Portal vein gas and pneumoperitoneum are less commonly seen (61,64). In a retrospective review of 141 COVID-19 patients in the ICU, 56% had clinically or radiologically diagnosed ileus, 2% had Ogilvie-like syndrome, 4% had bowel ischemia (3% small bowel, 1% small and large bowel and 1% cecal), 11% had GI bleeding and 4% had Clostridium difficile colitis (60).…”
Section: Bowel Imaging Patterns Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Another retrospective study included 81 COVID-19 patients with abdominal CT, and 45 (55%) had positive abdominopelvic findings. The most common abdominal imaging features were intestinal imaging findings (24%), including colorectal (5%) and small bowel thickening (12%), intestinal distension (18%), pneumatosis (1%), and intestinal perforation (1%)[ 79 ]. Morparia et al [ 80 ] reported abdominal imaging findings in critically ill children admitted with multisystem inflammatory syndrome associated with COVID-19.…”
Section: Abdominal Imaging Findings In Covid-19 Patientsmentioning
confidence: 99%